(untitled) (Productivity, 2023)
This study aims to determine the effect of service quality and product quality on customer satisfaction at Billy Coffee House in the Mega Mas Manado area. This study uses a quantitative method with multiple regression analysis techniques. The data used in this study are primary and secondary data. Primary data were obtained by asking consumers directly using a structured questionnaire, while secondary data were obtained from the business owner involved in this study. The statistics obtained show that all questionnaires in this study are valid and reliable with a sample size of 50 respondents. By conducting statistical tests, instrument tests, classical assumption tests, hypothesis tests, and determination tests (R2), the results of the data processing showed that service quality and product quality had a 53.2% greater effect on customer satisfaction than the remaining 46.8% at Billy Coffee House in the Mega Mas area of Manado.